Interactive Multimedia as a Catalyst for Improving Students’ Mathematical Problem-Solving Ability - Nur Wasi'ah; Adi Nur Cahyono (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
Students in Indonesia often have difficulties in mathematics problem-solving, mainly due to the absence of engaging media in traditional teaching techniques. This study aimed to examine the effect of interactive learning multimedia on students' mathematical problem-solving skills. We performed a Systematic Literature Review (SLR), examining 20 papers, of which 15 were selected from accredited national journals (Sinta 1-5) sourced from Scopus and Google Scholar, with a specific emphasis on "interactive learning multimedia" and "mathematical problem-solving ability." The results repeatedly indicated that interactive learning multimedia substantially improves students' mathematical problem-solving abilities. Integrating interactive multimedia, especially within a Problem-Based Learning (PBL) framework, shown significantly greater efficacy than traditional training devoid of such media. In conclusion, interactive learning multimedia is a crucial instrument for enhancing mathematics instruction and cultivating students' critical problem-solving skills.